2011
DOI: 10.1111/j.1532-5415.2011.03502.x
|View full text |Cite
|
Sign up to set email alerts
|

Number of Teeth and Fatigue in Older Adults

Abstract: Tooth loss is associated with onset of fatigue in old age, but the estimates are attenuated when adjusting for socioeconomic position and smoking. Tooth loss may be an early indicator of frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 33 publications
3
59
0
5
Order By: Relevance
“…The results support previous research that links poor dentition to physical impairments [6, 810, 15, 16]. Tooth loss may be an indicator of low physiological reserve [29] resulting from cumulative effects of unfavorable exposures throughout the life course, which also has adverse effects on walking speed. Common risk factors for periodontitis and walking speed decline are, for example, lifestyle-related factors such as smoking and obesity [30].…”
Section: Discussionsupporting
confidence: 88%
“…The results support previous research that links poor dentition to physical impairments [6, 810, 15, 16]. Tooth loss may be an indicator of low physiological reserve [29] resulting from cumulative effects of unfavorable exposures throughout the life course, which also has adverse effects on walking speed. Common risk factors for periodontitis and walking speed decline are, for example, lifestyle-related factors such as smoking and obesity [30].…”
Section: Discussionsupporting
confidence: 88%
“…There are few previous data on the association between oral health and some components of the frailty syndrome, but not with the frailty syndrome overall [34,35]. …”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the use of complete dentures and reports of chewing problems and loss of teeth are associated with fatigue (a component of frailty) and mortality in the elderly [34,35]. However, associations between other oral health conditions and frailty have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Najčešći razlozi gubitka zuba su: parodontopatije, karijes zuba, pogoršano opšte zdravstveno stanje bolesnika. Veoma su značajni i socioekonomski faktori kao što su: ''strah od doktora'', nemaran odnos prema oralnom zdravlju, visoka cijena intervencija, redukovan pristup stomatološkim ordinacijama, nizak nivo obrazovanja i pripadnosti nižim društvenim slojevima [9,12,20] Prema izvještaju SZO iz 2005. godine u Bosni i Hercegovini je bilo 78% bezubih osoba starijih preko 65 godina života, u Albaniji 69%, Bugarskoj 53%, Italiji 19% i Sloveniji 16% [21]. Rezultati meta-analize kojom je obuhvaćenо oko 1000 publikacija objavljenih na engleskom jeziku u posljednjih 20 godina (1990-2009) su pokazali da apsolutno sve analizirane studije potvrđuju negativni uticaj gubitka zuba na kvalitet života, nezavisno od mjesta gdje su sprovedene i od korišćene metodologije [12].…”
Section: Gubitak Zubaunclassified
“…Međutim, dokazano je da starost sama po sebi nije faktor koji značajno utiče na gubitak kosti alveoralnog grebena. Značajni faktori mogu biti: trajanje bezubosti, neadekvatan pritisak na kost zbog nošenja proteza, način ishrane, sistemske bolesti, osteoporoza, pripadnost ženskom polu i primjena lijekova [18,20,25,32,33,36,37].…”
Section: Resorpcija Kosti Alveoralnog Grebenaunclassified